Capsid size determination by Staphylococcus aureus pathogenicity island SaPI1 involves specific incorporation of SaPI1 proteins into procapsids - Poliakov, Anton (2008)
The Staphylococcus aureus pathogenicity island SaPI1 carries the gene for the toxic shock syndrome toxin TSST-1 and can be mobilized by infection with S. aureus helper phage 80α. SaPI1 depends on the helper phage for excision, replication and genome packaging. The SaPI1 transducing particles are comprised of proteins encoded by the helper phage, but have a smaller capsid commensurate with the smaller size of the SaPI1 genome. Previous studies identified only 80α-encoded proteins in mature SaPI1 virions, implying that the presumptive SaPI1 capsid size determination function(s) must act transiently during capsid assembly or maturation. In this study, 80α and SaPI1 procapsids were produced by induction of phage mutants lacking functional 80α or SaPI1 small terminase subunits. By cryo-electron microscopy, these procapsids have a rounded shape and an internal scaffolding core. Mass spectrometry (MS) was used to identify all 80α-encoded structural proteins in 80α and SaPI1 procapsids, including several that had not previously been found in the mature capsids. In addition, SaPI1 procapsids contained at least one SaPI1-encoded protein that has been implicated genetically in capsid size determination. MS on full-length phage proteins showed that the major capsid protein and the scaffolding protein are N-terminally processed in both 80α and SaPI1 procapsids.